Pentingnya peran orang tua dalam mendukung pendidikan anak - Sa'diyah, Lu'lu'atun Nadhirotus (Maliki Interdisciplinary Journal, 2024)
The smallest and most crucial unit in determining a person's personality is the family. Family members such as parents have an important role in influencing the attitudes and character of their offspring. Education is one of the most important aspects of a child's existence. Education includes social and ethical principles in addition to academic knowledge. Therefore, parents need to take a proactive role in advancing their children's education. The assistance that parents provide for their children's schooling is very important. Children's learning achievements and growth and development are greatly influenced by their parents. Parents can encourage their children to study harder and better by playing an active role in the educational process. By helping their children with schoolwork or supporting them in extracurricular activities that match their interests and skills, parents can help their children become better students. To ensure that their children get the direction and help they need while at school, parents can also develop strong contacts with teachers and other school staff members.